Measuring Continuous Assessment Competencies of Primary School Teachers - Ajayi , Olufemi Abiodun; Ajayi , Kassim Olusanmi; Akorede , Olufunbi Jimoh (African Journal of Education,Science and Technology (AJEST), 2015)
There is a popular saying that if you don’t know where you are going, you won’t know when you get there’. But there is more to it as you need to be aware of road signs which are guides that will make you know when you get there. This explains the position of continuous assessment (CA) in schools. This study is a survey type and it measured the continuous assessment literacy of primary school teachers using a sample of 102 teachers taken from two geographically contiguous local government areas. The only instrument for the study was Teacher Continuous Assessment Literacy Scale (TCALS) with four different subscales namely teachers’ knowledge (r = .90), teachers’ perception (r = .93), teachers’ attitude (r = .92), and teachers’ continuous assessment practice of (r = .91).The findings revealed that the teachers were highly literate in CA and that 64.3% of the variance in teachers’ CA practice is attributable to teachers’ knowledge, perception and attitude towards CA. Regression coefficients further show that of the three predictors the teachers’ perception of CA has the most significant contribution(β = .504) followed by teachers’ knowledge (β = .290) to the criterion variable. It is recommended amongst others that government units and agencies responsible for the training and retraining of teachers should send teachers out on periodic workshop in order for them to update their knowledge of continuous assessment practice